Common 894G>T single nucleotide polymorphism in the gene coding for endothelial nitric oxide synthase (eNOS) and risk of congenital heart defects - van Beynum, Ingrid M.; Mooij, Christiaan; Kapusta, Livia; Heil, Sandra; den Heijer, Martin; Blom, Henk J. (Clinical chemistry and laboratory medicine, 2008)
Background: Endothelial nitric oxide synthase (eNOS) produces nitric oxide, which plays a role in vasodilatation and in the regulation of cell growth and apoptosis. eNOS-deficient mice have impaired cardiac development resulting in congenital heart defects (CHDs). In humans, a single nucleotide polymorphism in the gene coding for eNOS (894G>T) is associated with birth defects. Methods: We investigated the eNOS 894G>T polymorphism in relation to CHDs using a case-control study and a case-parent study. Possible interaction with maternal cigarette smoking during pregnancy and periconceptional folic acid supplementation was also investigated in a case-only approach. Results: The eNOS 894G>T polymorphism was genotyped in 170 CHD-affected children, in 161 of their mothers, 215 control children and 240 control women. For the case-parent study, 135 complete triads were available. The sum of eNOS 894 GT and TT vs. GG genotypes in children was associated with increased CHD risk [odds ratio, OR 1.5 (95% CI 1.03–2.31)]. There was no preferential transmission of the 894T allele [OR 1.2 (95% CI 0.81–1.69)]. Overall, the maternal eNOS 894 GT or TT vs. GG genotypes were not associated with increased CHD risk. The maternal 894TT genotype in combination with maternal smoking was associated with an increased risk, particularly for a subgroup of other than conotruncal heart defects [OR 3.3 (95% CI 1.00–11.1)]. No interaction with periconceptional folic acid supplementation was observed. Conclusions: Our data indicate that the eNOS 894G>T polymorphism is associated with increased CHD risk. The study also provides evidence of a possible gene-environment interaction effect on CHD risk between the maternal eNOS 894G>T variant and maternal cigarette smoking during pregnancy. This observation should be interpreted with caution because of the relatively small subgroups. Further study in a larger group of CHD subjects is required. Clin Chem Lab Med 2008;46:1369–75.